Study of Tradition Process of Constructing Gorontalo House for Gorontalo Culture - Kalih Trumansyahjaya; Lydia S. Tatura (Tesa Arsitektur, 2018)
The cultural form in architecture is an indication that the closer the work of architecture to the process of cultural creation. The work of architecture as an artifact is the final form arising from the existence of ideas and actions within a culture. The people of Gorontalo generally still hold the customary tradition in the process of building a house in Gorontalo which is a cultural idea and action that can reflect the traditional and cultural strength of Gorontalo people so that it can be used as a trace of Gorontalo architectural culture. This study aims to discuss the details of the implementation and understand how the process of building tradition in Gorontalo society based on technical, cultural and environmental aspects. The research method uses a qualitative approach as a process of collecting a number of actual and contextual field data to get a detailed picture. The process for analyzing the problem then uses descriptive and inductive research methods to focus its attention on actual phenomena and depicts in depth the conditions in the field. The result of this research is a thorough knowledge of traditional structural system of cultural process of building a house in Gorontalo society.